Analysis of Online Customer Review on Purchase Decisions with Customer Trust as Intervening - Alena, Vaya Nabilla; Hasanah, Yulia Nur (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
This internet service can be used in various fields, such as the use of the internet in the fields of economy, education, industry, telecommunications, and tourism to the field of beauty. Nowadays, the use of the internet is no stranger to finding information about beauty products. In this regard, it is necessary to discuss the influence of online customer reviews on purchase decisions through customer trust in Female Daily. This study aims to determine the effect of online consumer reviews on purchase decisions through trust as an intervening variable. The population in this study is the Indonesian people who have accessed the website Female Daily. The sample size in the study was 100 people, and the method used in this study was quantitative. The data collection method used is a questionnaire. The analytical method used in this research is path analysis. The results of the analysis in this study indicate that online customer reviews and customer trust have a significant effect on purchase decisions. Online customer reviews have a significant effect on customer trust. Customer trust can mediate online customer reviews of purchase decisions with a percentage of 84.5%.